Transparency of clinical practice guidelines: A mixed methods research - Wang, Xinyi; Long, Youlin; Hu, Tengyue; Yang, Zixin; Liu, Liqin; Yang, Liu; Cheng, Yifan; Gu, Ran; Shen, Yanjiao; Yang, Nan; Huang, Jin; Chen, Yaolong; et al. (Chinese medical journal, 2025)
The paucity of systematic research on guideline transparency makes it challenging for users to judge. [...]the current scoping review aimed to evaluate guideline transparency, summarizing and analyzing themes, relationships and factors to inform future practice. [...]we invited 11 experts with experience in developing guidelines on March 12, 2021, to discuss the themes of guideline transparency and build a relational model based on the results of data integration. [...]methods of evidence retrieval must be disclosed to enable evidence tracing, otherwise the guide may not be approved by users. [...]disclosure should include analysis of integrity, adequacy and authenticity.